Iron diffusivity into superconducting YBa2Cu3O7−δ at oxygen-assisted sintering: structural, magnetic, and transport properties. Issue 14 (November 2021) - Pęczkowski, Paweł; Zachariasz, Piotr; Kowalik, Marcin; Tokarz, Waldemar; Kumar Naik, Sugali Pavan; Żukrowski, Jan; Jastrzębski, Cezariusz; Dadiel, Longji Joseph; Tabiś, Wojciech; Gondek, Łukasz
Abstract: Optimization of materials exhibiting high-temperature superconductivity for producing controllable nano-devices is crucial for industrial applications. Herein we report a comprehensive study of the diffusion process between YBa2 Cu3 O7− δ (YBCO) and iron particles. Fe diffusion into the YBCO matrix could be fundamental for multilayer systems with YBCO/Fe-alloy interfaces. We have found that the orthorhombic YBCO structure adopts to 3 wt% Fe, while for higher Fe content, a formation of BaFeO3− δ and iron oxides was observed. Complementary measurements confirmed the strong superconductivity suppression in YBCO-Fe materials containing more than 7 wt% Fe. The YBCO with diffused Fe material retain the unit cell orthorhombicity (max. 3 wt% Fe), and their superconducting properties follow the principle of critical scaling with different exponents (γ). The critical current density ( J c ), pinning fields ( H P ) exhibit γ = 1, the first critical field ( H c1 ) shows γ = 1/2, and critical temperature ( T c ) demonstrates γ = 7/4.